Partizipation im alltäglichen Unterricht durch Kooperation und Individualisierung in heterogenen Klassen – ein Beitrag zur Demokratiebildung? - Hildebrandt, Elke; Campana, Sabine (International Dialogues on Education Journal, 2016)
In order to constitute and develop democracy school’s central task is the promotion of childrens’ participation skills. Being able to promote the ability to self- and co-determination as well as solidarity (Klafki 1996) in upcoming generations, nationally and internationally, is an important step towards a free, peaceful life, founded on maturity. The Convention on the Rights of the Child (UN, 1989) was ratified in 1990. All signing states have agreed to further the right toof participation of children. However studies show that participation in socialization spaces such as school, albeit theoretically aimed at, is in fact only marginally implemented (Raby, 2008; Thornberg & Elvstrand, 2012). Often participation is limited to temporary projects and extra-curricular offerings. These approaches appear to be merely stagings of participation, which could potentially be the reason why children experience a lack of participation in school (Rieker, 2014). This paper addresses the question of how cooperative and individualized teaching can contribute to promoting participation skills.